Dysonans ludonarracyjny w światocentrycznych grach wideo - Mróz, Michał (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
The author explores the issue of “ludonarrative dissonance”, a term developed by the game designer C. Hocking in his critique of the game BioShock. The author explains Hocking’s arguments and then expands on the term, disagreeing with Hocking. In the case of BioShock, the author interprets the dissonance not as a design flaw but as a deliberate narrative strategy that momentarily distances the player from the game’s fiction to emphasize its metanarrative dimension. The author argues that ludonarrative dissonance is itself part of videogame poetics, thus echoing the works of F. Seraphine and P. Grabarczyk & B.W. Kampmann. The author then examines how ludonarrative dissonance may appear in vast, nonlinear open-world cRPGs. An analysis of examples from The Elder Scrolls: Skyrim, Fallout 3, and Fallout 4 reveals various instances of unintended dissonance. Finally, the author compares these games to Fallout: New Vegas, presenting it as an example of harmonizing the narrative – the main motifs and story – with the narrativity of gameplay, including rules, mechanics, and vast player agency.